Comparison of cardiovascular disease risk in women with and without breast cancer: secondary data analysis with the 2014-2018 korean national health and nutrition examination survey - Seongmi Choi; Na-Jin Park; Mihui Kim; Kijun Song; JiYeon Choi (BMC, 2023)
Abstract Background Aging breast cancer survivors may be at an elevated risk of cardiovascular disease (CVD), but little is known about CVD risk assessment and breast cancer in Korean women. We hypothesized that Korean breast cancer survivors would have higher risks of future CVD within the next 10 years (i.e., Framingham Risk Score [FRS]) than women without cancer. Objectives (1) To compare FRS-based CVD risks in women with and without breast cancer based on propensity score matching; and (2) To explore adiposity-related measures in relation to FRS in Korean women with breast cancer. Methods Using the cross-sectional data from the 2014-2018 Korean National Health and National Survey (KNHANES), we identified 136 women with breast cancer aged 30-74 years who had no other cancer and no CVD. The comparison group of 544 women with no cancer were selected by 1:4 nearest-neighbor propensity score matching based on breast cancer diagnosis. CVD risk was assessed by FRS based on multiple traditional risk factors (e.g., cholesterol, blood pressure, diabetes, and smoking). Adiposity was measured by physical examination, including body mass index (BMI) and waist-to-height ratio (WHtR). Physical activity and health behaviors were assessed by self-reports. Results Women with breast cancer (mean age of 57 years) had similar FRS levels at a low-risk category (< 10%) to women with no cancer (4.9% vs. 5.5%). Breast cancer survivors (mean 8.5 survival years) presented at significantly lower levels of total cholesterol, BMI, and WHtR (all p values < 0.05) than their counterpart. Within the breast cancer group, WHtR ≥ 0.5 was associated with higher FRS, compared to WHtR < 0.5. FRS was not different by survival < 5 years or ≥ 5 years after breast cancer diagnosis. Conclusions FRS-based CVD risks were not different in Korean, mostly postmenopausal, women by breast cancer status. Whereas breast cancer survivors had even lower levels of lipid and adiposity measures than women without cancer, those values indicating borderline cardiometabolic risk suggest continued screening and management efforts for these aging women. Future studies are needed to examine longitudinal trajectories of CVD risk factors and CVD outcomes among Korean breast cancer survivors.